2019
DOI: 10.2196/11509
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Therapist-Supported, Mobile Phone–Delivered Online Intervention for Depression: Longitudinal Observational Study

Abstract: BackgroundDepression is a very common condition that impairs functioning and is often untreated. More than 60% of the treatments for depressive disorder are administered in primary care settings by care providers who lack the time and expertise to treat depression. To address this issue, we developed Ascend, a therapist-supported, mobile phone–delivered 8-week intervention administered at the Meru Health Online Clinic in Finland.ObjectiveWe conducted two pilot studies to examine the feasibility of the Ascend i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 23 publications
6
56
0
1
Order By: Relevance
“…An important but largely unanswered question is who is likely to benefit the most from app-based psychological interventions, and what factors are predictive of the degree to which individuals benefit over time. Our previous feasibility study suggested that a greater volume of app-based practice predicted the occurrence of fewer depressive symptoms 4-weeks after completing the Ascend intervention 38 . In the present study, the degree of engagement with Ascend did not impact depression or anxiety scores at 6-or 12-months post-intervention, though this analysis was likely underpowered due to a large proportion of missing data at these time-points.…”
Section: Principal Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…An important but largely unanswered question is who is likely to benefit the most from app-based psychological interventions, and what factors are predictive of the degree to which individuals benefit over time. Our previous feasibility study suggested that a greater volume of app-based practice predicted the occurrence of fewer depressive symptoms 4-weeks after completing the Ascend intervention 38 . In the present study, the degree of engagement with Ascend did not impact depression or anxiety scores at 6-or 12-months post-intervention, though this analysis was likely underpowered due to a large proportion of missing data at these time-points.…”
Section: Principal Findingsmentioning
confidence: 99%
“…The Meru Health Ascend intervention has been described in detail previously 38 Participants are enrolled in groups of between 10-15 individuals that work through the intervention at the same time, and can provide anonymous support to one another via a discussion board within the app. Specifically, participants can post anonymous reflections on practices and lessons to the discussion board, to which their therapist can respond freely, and to which other group members can respond with pre-written empathy statements and/or emoticons.…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Content delivered in the weekly modules is derived from several evidence-based treatments for depression including Mindfulness-Based Meditation (MM) 14,15 , Cognitive-Behavioral Therapy (CBT) 16 , and Behavioral Activation Therapy (BAT) 17 delivered via texts, videos, and daily practices. Analyses of this program have indicated post-intervention clinically significant reductions in depressive symptoms that remain at 6-and 12-month follow-up assessments 18,19 .…”
Section: Introductionmentioning
confidence: 99%